Operational Risk Management Design In The Indonesia Mining Growth Program (P3I) Using House Of Risk Method - Mangasa Siregar; Suparno Suparno (Institut Teknologi Sepuluh Nopember, 2020)
The Indonesia Mining Growth Program (P3I) is a development project activity for nickel Mining Enterprise and Processing Plant in the